INVITATION TO PARTICIPATE: IV INTERNATIONAL CONFERENCE "FOREIGN LANGUAGE OF PROFESSION AND PROFESSIONAL IDENTITY" (Živi jezici: Journal for Foreign Languages and Literatures, 2016)
The Association for Foreign Languages and Literatures of Serbia, the Section of University Teachers of Foreign Languages and the Teacher Education Faculty of the University of Belgrade are organizing the Fourth International Conference dedicated to foreign languages, which will be held on September 29 and 30, 2017 at the Faculty of Teacher Education.
Keywords: foreign language of profession; professional identity; international conference